Empowering teachers in the Kepulauan Seribu through innovation-based learning strategies - Puspo Dewi Dirgantari; Raden Dian Herdiana Utama; Masharyono Masharyono; Lili Adi Wibowo; Yusuf Murtadlo; Ery Adam Primaskara; Bambang Widjajanta; Girang Razati; B. Lena Nuryanti; Mazaya Izzatur Rahim (Jurnal Abmas, 2025)
Education in remote island regions, such as the Kepulauan Seribu, faces unique challenges due to geographical isolation, limited infrastructure, and unequal access to technology, creating disparities in learning quality compared to urban areas. Teachers in this region often lack access to professional development programs. This community service (PkM) program was designed to improve the competence of 15 teachers (Elementary, Junior, Senior High) in implementing creative and innovative learning strategies adapted to the local context. Using a Participatory Action Research (PAR) approach, the program involved five stages: needs identification, innovative model design (including blended learning and project-based learning), intensive training via workshops and micro-teaching, implementation, and mentoring and evaluation. The results showed that teachers became more confident in utilizing available simple technology and were able to design contextual learning strategies based on local potential, such as marine ecosystems or tourism. Teachers also successfully applied interactive methods to increase student engagement and found the mindful, meaningful, joyful learning approach highly suitable for creating a positive classroom atmosphere. This program concludes that strengthening teacher capacity through adaptive strategies effectively enhances competence and offers a replicable educational empowerment model for other remote (3T) regions.   Abstrak Pendidikan di wilayah kepulauan terpencil seperti Kepulauan Seribu menghadapi tantangan khas berupa isolasi geografis, infrastruktur terbatas, dan kesenjangan akses teknologi, yang berdampak pada disparitas kualitas pembelajaran dibandingkan daerah perkotaan. Guru di wilayah ini seringkali memiliki keterbatasan akses terhadap program pengembangan profesional. Kegiatan pengabdian kepada masyarakat (PkM) ini dirancang untuk meningkatkan kompetensi 15 guru (SD, SMP, SMA) dalam menerapkan strategi pembelajaran kreatif dan inovatif yang disesuaikan dengan konteks lokal. Menggunakan pendekatan Participatory Action Research (PAR) , program ini dilaksanakan melalui lima tahap: identifikasi kebutuhan, perancangan model inovatif (mencakup blended learning dan project-based learning), pelatihan intensif melalui workshop dan micro-teaching, implementasi, serta pendampingan dan evaluasi. Hasil kegiatan menunjukkan bahwa guru menjadi lebih percaya diri memanfaatkan teknologi sederhana yang tersedia dan mampu merancang pembelajaran kontekstual berbasis potensi lokal, seperti ekosistem laut atau pariwisata. Guru juga berhasil menerapkan metode interaktif untuk meningkatkan keterlibatan murid, serta menilai pendekatan mindful, meaningful, joyful learning sangat sesuai untuk menciptakan suasana kelas yang menyenangkan. Program ini menyimpulkan bahwa penguatan kapasitas guru melalui strategi adaptif efektif meningkatkan kompetensi dan menawarkan model pemberdayaan pendidikan yang dapat direplikasi di daerah 3T lainnya. Kata Kunci: Bauran pembelajaran; pembelajaran kontekstual; pemberdayaan guru; pendidikan daerah terpencil; pengabdian kepada masyarakat; strategi pembelajaran inovatif.